PERAN KEPALA SEKOLAH DALAM MENINGKATKAN PROFESIONALISME GURU SLB N 1 SLEMAN (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
This study aimed to describe the principal's role in improving the professionalism of teachers in SLB N 1 Sleman, and to investigate the factors supporting or inhibiting factors anything contained in the school in relation to improving the professionalism of teachers in special schools NI Sleman.The method used is qualitative research that emphasizes the depth of information or meaning. Qualitative methods in this research is to gain a more complete data, depth, credible, and meaningful about SLB Negeri 1 Sleman. The reason for choosing the location of this study are striking differences in achievement between schools SLB in Sleman. In this study used data observation and interview techniques to the source ie the Principals and staffs as well as educators and education in SLB N 1 Sleman. To test the data used triangulation of data sources were analyzed by means of inductively to obtain meaningful conclusions.This study found a close relationship between the two variables, namely the role of the school principal and teacher professionalism. The role of principals include as, educator, manager, administrator, supervisor, leader, innovator, motivator, and interpreneur ( EMASLIM ) in improving the professionalism of teachers in SLB N 1 Sleman. The factors supporting or inhibiting factors faced by principals in their role in improving the professionalism of teachers in SLB N 1 Sleman .